Phosphoric acid modified attapulgite material as well as preparation method and application thereof
By modifying the concave and convex rod material with potassium dihydrogen phosphate, the problem of insufficient adsorption performance of concave and convex rods in the prior art is solved, and the efficient and selective heavy metal adsorption effect is achieved, and the process flow is simplified and the cost is reduced.
Patent Information
- Application Number
- CN202510090265.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-18
AI Technical Summary
The existing concave and convex rod adsorption materials have weak adsorption properties on heavy metals in water bodies, and the modification method is complex, time-consuming and costly.
By stirring and reacting the concave and convex rod ore powder with potassium dihydrogen phosphate in a solvent medium at 60~90°C, a phosphoric acid modified concave and convex rod material is formed, which improves its specific surface area and adsorption active site.
It realizes efficient adsorption of heavy metal ions in aqueous solution, especially high adsorption selectivity and capacity for lead ions and cadmium ions, and has simple process, low cost and short time, making it suitable for industrial production.
Smart Images

Figure CN119838560A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an adsorption material, in particular to a phosphoric acid modified attapulgite material, and also to a phosphoric acid modified attapulgite material and application thereof in adsorbing heavy metals in water, belonging to the field of water pollution treatment. Background Art
[0002] Water is the basis for the survival of all organisms and is of vital importance to ecosystems, human society and economic development. However, rapid industrialization, urbanization and population growth in recent centuries have led to increased water pollution. Heavy metal ions (such as lead and cadmium) are one of the main pollutants in water bodies, which pose a major threat to ecosystems and human health and can cause health problems such as poisoning and disease through accumulation in the food chain. Therefore, it is crucial to remove heavy metal ions such as lead and cadmium from water.
[0003] The main methods for controlling heavy metal pollution include adsorption, precipitation, oxidation-reduction and bioremediation. Adsorption has become a widely used technology due to its low cost, strong selectivity, wide application range and simple operation. In recent years, clay mineral adsorption materials have become one of the research hotspots of adsorption materials due to their abundant sources and low prices. Attapulgite is a special clay mineral with a slender rod or fiber structure, a high specific surface area and good adsorption capacity, and has been widely used in many fields. However, the adsorption performance of the original attapulgite ore has not yet reached the ideal optimal effect, and its adsorption performance for heavy metals in water is relatively weak.
[0004] In the prior art, the modification method of attapulgite has the problems of complex operation, long reaction time, and no obvious performance improvement. A Chinese patent (publication number: CN102247807A) discloses a method for preparing a modified attapulgite adsorption material. The method requires the use of multiple reagents such as aminosilane coupling agent, excess acrylate, polyethylene polyamine or alcohol amine for step-by-step reaction, and finally the reaction reagents are removed by reduced pressure distillation to obtain the finished product. The modified attapulgite can improve its adsorption capacity for various heavy metals, but it has high energy consumption, high cost and complex operation. Summary of the invention
[0005] In view of the defects of the prior art, the first object of the present invention is to provide a phosphoric acid-modified attapulgite material, which not only has abundant pores and a high specific surface area, but also has phosphate-modified adsorption active sites, and exhibits high adsorption activity and adsorption selectivity for heavy metal ions in aqueous solution.
[0006] The second object of the present invention is to provide a method for preparing a phosphoric acid-modified attapulgite material, which is simple to operate, low-cost, short in time, and is conducive to industrial production.
[0007] The third object of the present invention is to provide an application of a phosphoric acid-modified attapulgite material, which is used to adsorb heavy metal ions in aqueous solution. It has the characteristics of large adsorption capacity, fast rate, good adsorption selectivity, etc., and is particularly suitable for the treatment of wastewater contaminated by lead ions and cadmium ions.
[0008] In order to achieve the above technical purpose, the present invention provides a method for preparing a phosphoric acid-modified attapulgite material, wherein attapulgite powder and potassium dihydrogen phosphate are stirred and reacted in a solvent medium at a temperature of 60-90°C, and the solid product is separated and dried to obtain the material.
[0009] The key to the phosphoric acid-modified attapulgite material provided by the present invention is to achieve modification by using attapulgite powder and potassium dihydrogen phosphate through a reaction under appropriate temperature conditions. The solvent medium is used in the reaction process to clear the adsorption channels of the attapulgite powder, thereby increasing its specific surface area, thereby greatly improving its ability to quickly adsorb and enrich heavy metal ions in aqueous solution. At the same time, through the infiltration of phosphate ions at high temperature during the reaction process, phosphate can be uniformly and stably loaded on the surface and pores of the attapulgite powder to form adsorption active sites for heavy metal ions, so that the heavy metal ions adsorbed on the surface and pores of the attapulgite powder are quickly mineralized by the phosphate loaded in the attapulgite powder, thereby improving the activity and adsorption capacity of the attapulgite in adsorbing heavy metal ions. In particular, lead ions and cadmium ions in aqueous solution can be mineralized by phosphate to form lead phosphate and cadmium phosphate precipitates. The solubility product Ksp of these minerals is extremely small, all within 10 -15 The present invention selects potassium dihydrogen phosphate as a modifier, mainly because potassium dihydrogen phosphate has high solubility in water, can be quickly dissolved in water, form a uniform solution, better contact and react with the attapulgite powder, and compared with phosphoric acid or other phosphates, potassium dihydrogen phosphate is neutral or weakly acidic when dissolved in water, and can maintain the structure of the attapulgite itself while introducing phosphate ions, so as to avoid the damage of the attapulgite structure and the decrease of adsorption capacity.
[0010] As a preferred solution, the mass ratio of the attapulgite powder to the potassium dihydrogen phosphate is 1:0.1~1. The ratio of potassium dihydrogen phosphate should be controlled within an appropriate range. If its ratio is too low, the phosphate loaded in the attapulgite mineral will be less. If its ratio is too high, the pores of the attapulgite mineral will be blocked. Therefore, the content of potassium dihydrogen phosphate will affect its adsorption performance for heavy metals. The mass ratio of the attapulgite powder to the potassium dihydrogen phosphate is further preferably 1:0.2~0.5.
[0011] As a preferred solution, the mass volume ratio of the attapulgite powder to the solvent medium is 1-2 g: 100-200 mL. A high ratio of the solvent medium can fully wet and swell the attapulgite powder, which is beneficial to the removal of impurities in the attapulgite powder and the internal modification.
[0012] As a preferred solution, the solvent medium is deionized water and / or anhydrous ethanol. Deionized water and / or anhydrous ethanol are preferably used as the solvent medium, mainly because these polar solvents have good wetting properties on the attapulgite, which is beneficial to the removal of impurities in the pores of the attapulgite, and at the same time, it is beneficial to enhance the penetration of phosphate into the interior of the attapulgite and improve the uniformity of phosphate loading.
[0013] As a preferred solution, the conditions of the solvent thermal reaction are: temperature of 70-85°C, stirring rate of 100-300rpm, and time of 4-5h. At this temperature, the activity of potassium dihydrogen phosphate molecules is improved, the reaction rate is accelerated, and the reaction process between potassium dihydrogen phosphate and attapulgite powder is faster, thereby improving the modification efficiency. At the same time, under the preferred temperature conditions, the expansion of the attapulgite pores increases its active sites, further improving the modification effect of phosphate on it.
[0014] The method for preparing the phosphoric acid-modified attapulgite material provided by the present invention comprises the following specific steps: (1) Take attapulgite powder and deionized water and / or anhydrous ethanol, measure them according to a mass volume ratio of 1-2 g: 100-200 mL, and mix them by ultrasonic mixing for 15-60 min to obtain a attapulgite suspension.
[0015] (2) adding potassium dihydrogen phosphate to the attapulgite suspension to obtain a mixed solution; the mass of the added potassium dihydrogen phosphate is 10% to 100% of the mass of the attapulgite raw material.
[0016] (3) Heat the mixed solution to 70-85°C, stir at a rate of 100-300 rpm, and react for 4-5 h.
[0017] (4) After the reaction is completed, the mixture is cooled and centrifuged for washing. The obtained precipitate is dried, ground, and sieved to obtain a phosphoric acid-modified attapulgite material. Deionized water and / or anhydrous ethanol are used for centrifugal washing, the centrifugal speed is 6000-8000 rpm, and the washing times are 2-5 times. The precipitate is vacuum dried at 60° C., ground, and passed through a 200-mesh sieve. The sieved material is the phosphoric acid-modified attapulgite material.
[0018] The invention also provides a phosphoric acid-modified attapulgite material, which is obtained by the preparation method.
[0019] The invention also provides an application of a phosphoric acid-modified attapulgite material, which is used for adsorbing heavy metal ions in an aqueous solution.
[0020] As a preferred embodiment, the heavy metal ions include lead ions and / or cadmium ions. The phosphoric acid-modified attapulgite material has selectivity for the adsorption of heavy metal ions such as lead ions and cadmium ions. For example, the aqueous solution may also include conventional metal ions such as calcium ions, sodium ions, and magnesium ions, which do not affect the adsorption performance of the phosphoric acid-modified attapulgite material for lead ions and cadmium ions. It should be particularly noted that the phosphoric acid-modified attapulgite material has a much greater adsorption selectivity for lead ions than for cadmium ions in a solution system where lead ions and cadmium ions coexist, which is unexpected.
[0021] As a preferred solution, the pH of the aqueous solution is 3.5-6.5, and the temperature is 35-65° C. Within the preferred pH and temperature range, as the pH increases and the temperature increases, the adsorption performance of heavy metal ions increases significantly, but the increase trend gradually slows down. Therefore, within the preferred pH and temperature range, it is beneficial to improve the adsorption performance of heavy metal ions.
[0022] With respect to the prior art, the technical solution of the present invention has the following beneficial technical effects: (1) The present invention uses potassium dihydrogen phosphate to modify the attapulgite, thereby providing more active sites for the attapulgite and optimizing its physical and chemical properties, thereby improving its adsorption capacity for heavy metal ions. In addition, the phosphoric acid-modified attapulgite material has a higher selectivity for lead ions, thereby improving the adsorption selectivity of the attapulgite.
[0023] (2) The present invention uses potassium dihydrogen phosphate as a modifying agent, which has a better modification effect than phosphoric acid or other phosphates, and has excellent water solubility and can be easily washed away. In addition, the non-toxic nature of potassium dihydrogen phosphate ensures its safety during use and is harmless to humans and the ecosystem.
[0024] (3) The present invention achieves the modification of attapulgite materials through a one-step reaction. This method is not only highly efficient but also economical. Compared with other existing modification methods, the entire process of this method is short in time and can usually be completed within a relatively tight time frame, which greatly improves production efficiency. At the same time, the operation of this process is relatively simple and can be carried out smoothly even at a low technical level. The equipment and materials involved are relatively easy to obtain, thereby effectively reducing the modification cost. This provides convenience for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the SEM image of the phosphoric acid-modified attapulgite material in Example 1.
[0026] Figure 2 This is the SEM image of the attapulgite ore in Comparative Example 1.
[0027] Figure 3 The phosphoric acid-modified attapulgite material in Example 1 has a Pb 2+ removal rate.
[0028] Figure 4 is the Cd content of the phosphoric acid-modified attapulgite material at different pH values in Example 1 2+ Adsorption amount.
[0029] Figure 5 is the Pb content of the phosphoric acid-modified attapulgite material at different concentrations in Example 2 2+ 、Cd 2+ Adsorption amount.
[0030] Figure 6 The phosphoric acid-modified attapulgite material in Example 2 is 2+ In the presence of Pb 2+ The adsorption amount.
[0031] Figure 7 The phosphoric acid-modified attapulgite synthesized with different reagents in Example 3 has a significant effect on Pb 2+ 、Cd 2+ The adsorption amount.
[0032] Figure 8 The phosphoric acid-modified attapulgite synthesized at different reaction temperatures in Example 4 changes with time to Pb 2+ The adsorption amount.
[0033] Fig. 9 The attapulgite ore in Comparative Example 1 was prepared at different Ca 2+ In the presence of Pb 2+ The adsorption amount. DETAILED DESCRIPTION
[0034] The content of the present invention is further described in detail below in conjunction with specific embodiments, but the following specific embodiments do not limit the protection scope of the claims of the present invention.
[0035] Example 1 (1) Obtaining a attapulgite suspension: Weigh 1 g of attapulgite raw ore powder and add it into 100 mL of deionized water. Stir it evenly with a glass rod and then perform ultrasonic mixing for 60 min to obtain a attapulgite suspension. (2) Liquid phase reaction preparation: 0.3 g of potassium dihydrogen phosphate was added to the attapulgite suspension to obtain a mixed solution. The mixed solution was heated to 70° C. in a water bath and stirred at a stirring rate of 200 rpm for 5 h.
[0036] (3) Drying the attapulgite: After the reaction is completed, the mixed solution is cooled and centrifuged three times at a centrifugal speed of 6000 rpm. Deionized water is added for washing in the last two centrifugations. The centrifuged precipitate is dried in a vacuum at 60°C, ground, and passed through a 200-mesh sieve. The sieved material is the phosphoric acid-modified attapulgite material. The SEM image of the phosphoric acid-modified attapulgite material is shown in Figure 1 ,and Figure 2 In contrast, the structure of the phosphoric acid-modified attapulgite material was not destroyed.
[0037] (4) Pd adsorption 2+ : Take 50mL of 20mg / L Pd 2+ The solution was placed in a 200 mL opaque plastic bottle, with a total of 5 portions as controls. After adjusting the solution pH to 5.5, 25 mg of phosphoric acid-modified attapulgite material was added. The solution system was reacted at 15°C, 25°C, 35°C, 45°C, and 55°C at a speed of 200 rpm for 8 h. After the adsorption reaction was completed, the supernatant was filtered and tested to calculate the Pd 2+ The results show that phosphoric acid modified attapulgite has good adsorption capacity for Pd 2+ It shows good adsorption. As the temperature increases, the removal rate also increases. When the temperature is greater than 35℃, the removal rate of Pd 2+ The removal rate reaches more than 95%, and when the temperature is equal to 55℃, the removal rate is nearly 99%. Figure 3 .
[0038] (5) Adsorption of Cd 2+ : Take 50 mL of 20 mg / L Cd 2+ The solution was placed in a 200 mL opaque plastic bottle, and the pH of the solution was adjusted to 2.5, 3.5, 4.5, 5.5, and 6.5, respectively, and then 25 mg of phosphoric acid-modified attapulgite was added. The solution system was reacted at 25°C and 200 rpm for 8 h. After the adsorption reaction was completed, the supernatant was filtered and tested to calculate Cd 2+ The results show that phosphoric acid modified attapulgite has a strong adsorption capacity for Cd 2+ It shows good adsorption. As the pH increases, the adsorption amount also increases. When the pH is 6.5, the adsorption amount reaches 11.57 mg / g. Specific data are as follows Figure 4 .
[0039] Example 2 (1) Obtaining a attapulgite suspension: Weigh 2 g of attapulgite raw ore powder and add it into 200 mL of deionized water. Stir it evenly with a glass rod and then ultrasonically mix it for 30 minutes to obtain a attapulgite suspension. (2) Liquid phase reaction preparation: 0.6 g of potassium dihydrogen phosphate was added to the attapulgite suspension to obtain a mixed solution. The mixed solution was heated to 70° C. in a water bath and stirred at a stirring rate of 200 rpm for 5 h.
[0040] (3) Drying the attapulgite: After the reaction is completed, the mixed solution is cooled and centrifuged twice at a centrifugal speed of 8000 rpm. Deionized water is added for washing in the second centrifugation. The centrifugal precipitate is dried at 60°C in a vacuum, ground, and passed through a 200-mesh sieve. The sieved material is the phosphoric acid-modified attapulgite material.
[0041] (4) Pd adsorption 2+ 、Cd 2+ : Take 50mL of Pd with concentrations of 10, 20, 30, 50, 100, 150, 200mg / L 2+ or Cd 2+ The solution was placed in a 200 mL opaque plastic bottle, and 25 mg of phosphoric acid-modified attapulgite material was added after adjusting the solution pH to 5.5. The solution system was reacted at 200 rpm at 25°C for 8 h. After the adsorption reaction was completed, the supernatant was filtered and tested to calculate the Pd 2+ 、Cd 2+ The results show that as the concentration of heavy metal solution increases, the adsorption of Pd 2+ 、Cd 2+ The adsorption capacity of Figure 5 .
[0042] (5) Pd 2+ Optional: Take 50 mL Pd 2+ (concentration 20mg / L), Ca 2+ The mixed solution was placed in a 200 mL opaque plastic bottle, where Ca 2+ With Pd 2+ The mass ratio was 0, 0.1, 0.5, 1, 5, and 10. After adjusting the solution pH to 5.5, 25 mg of phosphoric acid-modified attapulgite was added. The solution system was reacted at 25 °C and 200 rpm for 8 h. After the adsorption reaction was completed, the supernatant was filtered and tested to calculate the Pd 2+ The results show that phosphoric acid modified attapulgite has a strong adsorption capacity for Pd 2+ showed good selectivity when Ca 2+ With Pd 2+ When the mass ratio is 5, the selectivity increases by 202.12%. Figure 6 .
[0043] Example 3 (1) Obtaining a attapulgite suspension: Weigh 2 g of attapulgite raw ore powder in four beakers respectively, add it to 200 mL of deionized water, stir evenly with a glass rod, and then ultrasonically mix for 30 minutes to obtain a attapulgite suspension; (2) Liquid phase reaction preparation: According to the properties of the modified agent, 0.6 g of potassium dihydrogen phosphate, trisodium phosphate, phosphoric acid, sodium metaphosphate and P-507 were added to the attapulgite suspension to obtain a mixed solution. The mixed solution was heated to 70°C and stirred at a stirring rate of 200 rpm for 5 h.
[0044] (3) Drying the attapulgite: After the reaction, the mixed solution was cooled and centrifuged 5 times at a centrifugal speed of 6000 rpm. The attapulgite modified by potassium dihydrogen phosphate, trisodium phosphate, phosphoric acid, and sodium metaphosphate was washed with deionized water, and the P-507 modified attapulgite was washed with ethanol. The centrifugal precipitate was vacuum dried at 60°C, ground, and passed through a 200-mesh sieve. The sieved material was the phosphoric acid-modified attapulgite material. The phosphoric acid-modified materials obtained by modification with different agents were recorded as KP-ATP, Na-ATP, P-ATP, NaP-ATP, and MP-ATP, respectively.
[0045] (4) Pd adsorption 2+ 、Cd 2+ :Measure 50 mL of 20 mg / L Pd 2+ or Cd 2+ The solution was placed in a 200 mL opaque plastic bottle, and 25 mg of KP-ATP, Na-ATP, P-ATP, NaP-ATP, and MP-ATP were added after adjusting the solution pH to 5.5. The solution system was reacted at 200 rpm at 25 °C for 8 h. After the adsorption reaction was completed, the supernatant was filtered and tested to calculate the Pd 2+ 、Cd 2+ Adsorption capacity. The results show that the adsorption effect of KP-ATP is better than other pharmaceutical modified materials. Specific data such as Figure 7 It can be seen that the attapulgite modified with potassium dihydrogen phosphate has high adsorption activity for both lead ions and cadmium ions, while the attapulgite modified with trisodium phosphate, phosphoric acid, and sodium metaphosphate either has poor adsorption effect for lead ions or poor adsorption effect for cadmium ions. This may be because the structure of the attapulgite is destroyed during the modification process using other phosphate reagents, resulting in a decrease in adsorption performance.
[0046] Example 4 (1) Obtaining a attapulgite suspension: Weigh 2 g of attapulgite raw ore powder in two beakers, add it to 200 mL of water, stir it evenly with a glass rod, and then ultrasonically mix it for 45 minutes to obtain a attapulgite suspension; (2) Liquid phase reaction preparation: 0.6 g of potassium dihydrogen phosphate was added to the attapulgite suspension to obtain a mixed solution. The mixed solution was heated to 25°C and 70°C, respectively, and stirred at a stirring rate of 200 rpm for 5 h.
[0047] (3) Drying the attapulgite: Referring to Example 1, the phosphoric acid-modified attapulgite materials obtained were recorded as KP-ATP25 and KP-ATP70, respectively.
[0048] (4) Pd adsorption 2+ :Measure 200 mL of 50 mg / L Pd 2+ The solution was placed in a 250 mL beaker, and 100 mg of KP-ATP25 and KP-ATP70 were added after adjusting the pH of the solution to 5. The solution system was reacted at 200 rpm at 25 °C for 8 h. The supernatant was filtered and tested at 30 min, 60 min, 120 min, 240 min, 360 min, and 480 min, and the Pd of KP-ATP25 and KP-ATP70 were calculated. 2+ The results showed that KP-ATP70 could adsorb Pd 2+ The adsorption effect is better than KP-ATP25. Specific data are as follows Figure 8 This indicates that the modification of attapulgite powder needs to be carried out at an appropriate temperature.
[0049] Comparative Example 1 Take 50 mL Pd 2+ , Ca 2+ The mixed solution was placed in a 200 mL opaque plastic bottle, where Ca 2+ With Pd 2+ (20 mg / L) with a mass ratio of 0, 0.1, 0.5, 1, 5, 10, and after adjusting the solution pH to 5.5, 25 mg of attapulgite ore was added (see the SEM image of the ore Figure 2 The solution system was run at 25 °C and 200 rpm for 8 h. After the adsorption reaction was completed, the supernatant was filtered and tested to calculate the Pd 2+ The results show that if the attapulgite is not modified, its adsorption of Pd 2+ The selectivity is poor. Specific data such as Fig. 9 .
Claims
1. A method for preparing a phosphoric acid-modified attapulgite material, characterized in that: After attapulgite powder and potassium dihydrogen phosphate are stirred and reacted in a solvent medium at a temperature of 60-90°C, the solid product is separated and dried to obtain the product.
2. The method for preparing a phosphoric acid-modified attapulgite material according to claim 1, characterized in that: The mass ratio of the attapulgite powder to the potassium dihydrogen phosphate is 1:0.1~1.
3. The method for preparing a phosphoric acid-modified attapulgite material according to claim 1, characterized in that: The mass volume ratio of the attapulgite powder to the solvent medium is 1-2 g:100-200 mL.
4. The method for preparing a phosphoric acid-modified attapulgite material according to claim 1 or 3, characterized in that: The solvent medium is deionized water and / or anhydrous ethanol.
5. The method for preparing a phosphoric acid-modified attapulgite material according to claim 1, 2 or 3, characterized in that: The reaction conditions are: temperature of 70-85° C., stirring rate of 100-300 rpm, and time of 4-5 h.
6. A phosphoric acid-modified attapulgite material, characterized in that: Obtained by the preparation method according to any one of claims 1 to 5.
7. The phosphoric acid-modified attapulgite material according to claim 6, characterized in that: Used to adsorb heavy metal ions in aqueous solutions.
8. The phosphoric acid-modified attapulgite material according to claim 7, characterized in that: The heavy metal ions include lead ions and / or cadmium ions.
9. The phosphoric acid-modified attapulgite material according to claim 7, characterized in that: The pH of the aqueous solution is 3.5-6.5, and the temperature is 35-65°C.
Citation Information
Patent Citations
Preparation method and usage of modified attapulgite adsorption material
CN102247807A
Method for adsorbing trace lead ions in water
CN104437416A
Soil conditioner for removing heavy metals in farmland soil and preparation method thereof
CN107903902A
Phosphate modified attapulgite magnetic passivator and use method thereof
CN111548795A
Soil modifier
JP2024019747A